2010
DOI: 10.1242/jcs.071555
|View full text |Cite
|
Sign up to set email alerts
|

Src-dependent phosphorylation of ROCK participates in regulation of focal adhesion dynamics

Abstract: SummaryWhen a cell migrates, the RhoA-ROCK-mediated contractile signal is suppressed in the leading edge to allow dynamic adhesions for protrusion. However, several studies have reported that RhoA is indeed active in the leading edge of a migrating cell during serum stimulation. Here, we present evidence that regulation of ROCKII phosphorylation at the Y722 site in peripheral focal contacts is crucial for controlling the turnover of the focal adhesion (FA) complex uncoupled from RhoA activation during serum-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 55 publications
3
51
0
1
Order By: Relevance
“…RHO signaling (spots 613 and 850), which is connected to SRC signaling also was activated (35). This activation most likely occurs via focal adhesion kinase (FAK) (spot 340) and protein kinase C (PKC) (spot 170) (36,37).…”
Section: K Pneumoniae Pneumonia Kinome Profilementioning
confidence: 99%
“…RHO signaling (spots 613 and 850), which is connected to SRC signaling also was activated (35). This activation most likely occurs via focal adhesion kinase (FAK) (spot 340) and protein kinase C (PKC) (spot 170) (36,37).…”
Section: K Pneumoniae Pneumonia Kinome Profilementioning
confidence: 99%
“…To facilitate podosome rosette formation, Rho and/or ROCK II are often found to be repressed in cells. For example, active Src represses the Rho-ROCK pathway by activating RhoGAP (Arthur et al, 2000;Roof et al, 2000) or directly phosphorylating and inhibiting ROCK II (Lee et al, 2010;Pan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These opposing effects of actomyosin on the turnover dynamics of focal adhesions potentially influence cell migration. Because there is a large variation in the reported lifetime of focal adhesions (Lee et al, 2010;Meenderink et al, 2010;Stricker et al, 2013), we speculate that the maturation and disassembly of focal adhesions might be modulated and coordinated by actomyosin contraction in a manner that differs between different cell types and/or under different conditions. In line with this idea, we found that treatment with a higher concentration (10 or 20 mM) of Y-27632 increased the cell migration rate (supplementary material Fig.…”
Section: Roles Of Actomyosin Contraction In Adhesion Dynamics and Celmentioning
confidence: 97%